Wheat aleurone polyphenols increase plasma eicosapentaenoic acid in rats - Ounnas, Fayçal (Co-Action Publishing, 2014)
METHODS: These studies were designed to assess whether wheat polyphenols (mainly ferulic acid [FA]) increased the very-long-chain omega-3 fatty acids (VLC n-3) [eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)] in rats. Wheat aleurone (WA) was used as a dietary source of wheat polyphenols. Two experiments were performed; in the first one, the rats were fed WA or control pellets (CP) in presence of linseed oil (LO) to provide alpha-linolenic acid (ALA), the precursor of VLC n-3. In the second one, the rats were fed WA or CP in presence of control oil (CO) without ALA. The concentrations of phenolic acid metabolites in urine were also investigated. RESULTS: The urinary concentration of conjugated FA increased with WA ingestion (p<0.05). Plasma EPA increased by 25% (p<0.05) with WA in the CO group but not in the LO group. In contrast, there was no effect of WA on plasma DHA and omega-6 fatty acids (n-6). Finally, both n-3 and n-6 in the liver remained unchanged by the WA. CONCLUSION: These results suggest that WA consumption has a significant effect on EPA in plasma without affecting n-6. Subsequent studies are required to examine whether these effects may explain partly the health benefits associated with whole wheat consumption.